Early development of emerging and English-proficient bilingual children at school entry in an Australian population cohort. (January 2014) - Goldfeld, Sharon; O'Connor, Meredith; Mithen, Johanna; Sayers, Mary; Brinkman, Sally
Children who enter school with limited proficiency in the language of instruction face a range of challenges in negotiating this new context, yet limited data have been available to describe the early developmental outcomes of this subpopulation in the Australian context. The Australian Early Development Index (AEDI) is a teacher-rated checklist that measures five important domains of child development: physical health and wellbeing, social competence, emotional maturity, language and cognitive skills, and communication skills and general knowledge. In 2009, the AEDI was completed for 97.5% of Australian children in their first year of schooling ( N = 261, 147; M = 5 years, 7 months of age), providing a unique opportunity to explore the cross-sectional associations between language background, proficiency in English, and early developmental outcomes at the population-level. Logistic regression analyses revealed that, compared to their peers from English-speaking backgrounds, bilingual children who were not yet proficient in English had substantially higher odds of being in the "vulnerable" range (bottom 10th percentile) on the AEDI domains ( OR = 2.88, p < .001, to OR = 7.49, p < .001), whereas English-proficient bilingual children had equal or slightly lower odds ( OR = .84, p < .001, to OR = .97, ns ). Future research with longitudinal data is now needed to establish causal pathways and explore long term outcomes.